The Influence of Audit Quality, Profitability, Liquidity, Solvency on Going Concern Audit Opinions: A Literature Review - Handayani, Tasyanari; Kusumaningtyas, Meisya; Pratiwi, Ratih; Suryanto, Esha; Manurung, Herlina (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This article aims to determine the impact of audit quality, profitability, solvency, and leverage on the going concern audit opinion. The literature review is crafted to pinpoint hypotheses between variables, employing documentary studies and utilizing quantitative methods with secondary data from prior articles. The findings indicate that audit quality, profitability, and liquidity variables do not exhibit a significant negative effect on the going concern audit opinion. However, the solvency variable is identified to have a positive influence on the going concern audit opinion. These outcomes imply that maintaining high audit quality, ensuring profitability and liquidity, while managing solvency effectively, are crucial elements in forming a comprehensive and accurate assessment of a company's ability to sustain operations. These insights contribute to refining audit practices and decision-making processes for stakeholders, fostering a more robust foundation for corporate governance and financial reporting.